Fading and graphite nucleation sites in grey iron inoculated using silicon carbide (2017)
ABSTRACT: The most commonly used inoculants for producing grey iron are ferrosilicon based, but also there are reports indicating that silicon carbide can act as inoculant. There are few published studies of fading and nucleation sites of graphite when silicon carbide is used as inoculant, thus the understanding of the inoculation effect of silicon carbide is incomplete. To study these two aspects, fading and graphite nucleation sites, an ASTM class 35B grey iron inoculated with silicon carbide was produced and characterized. The results were compared with an ASTM class 35B grey iron inoculated with a ferrosilicon base inoculant and without inoculation. It was found that the effect of the silicon carbide was comparable to the ferrosilicon base inoculant and fading was similar. In addition, the graphite nucleation sites in the grey iron inoculated with silicon carbide were irregular shaped manganese sulfides larger than the nuclei in the grey iron inoculated with ferrosilicon, which suggest a similar nucleation mechanism for both inoculants.